A novel application of nylon membranes for tributyltin determination in complex environmental samples by fluorescence spectroscopy and multivariate calibration - Bravo, Manuel A. (2015)
The widely distributed pollutant tributyltin (TBT) was analyzed in different environmental samples (waters and sediments) combining preconcentration on a nylon membrane, excitation–emission fluorescence matrices directly measured over the membrane and second-order multivariate calibration. The latter was implemented using unfolded partial least-squares with residual bilinearization (U-PLS/RBL), a flexible algorithm achieving second-order advantage, even under severe spectral overlapping among sample components. Matrix-specific calibrations were required to overcome matrix effects, resulting in good analytical performance. TBT was determined in the concentration ranges 0.043–1.42 ng Sn mL− 1 in water and 24–400 μg Sn kg− 1 in sediments, with adequate detection limits in the range 0.03–0.15 ng Sn mL− 1.